Legal and Ethical Void in the Implementation of Stem Cell Technology in Indonesia - Lia Marliana; Evita Isretno Israhadi (PT. Publikasiku Academic Solution, 2024)
This study examines the legal gaps and ethical challenges in stem cell technology utilization in Indonesia. Stem cell technology in embryonic stem cells offers great potential in the medical field but also faces controversies and complex regulatory issues. The study identifies the legal gaps in current regulations and their impact on legal certainty for researchers, medical practitioners, and patients. It also analyzes the limitations of existing rules and proposes legal reformulation to address rapid technological developments and emerging ethical issues. The methodology in this study uses normative legal methods with legislative and analytical approaches to evaluate regulations related to stem cells in Indonesia. The findings of this study are expected to guide effective regulatory reform to support safe and ethical innovation of stem cell technology in Indonesia. It concludes that the legal void in stem cell technology regulation creates challenges such as uncertainty for stakeholders, security and ethical risks, and hindered research progress, necessitating comprehensive legal reform to establish clear guidelines, update security standards, integrate ethics, ensure transparency, and align with international standards to support safe innovation and protect public welfare.